2022
DOI: 10.1002/adfm.202206157
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Response and NIR‐II Photonic Thermal Co‐Enhanced Catalytic Therapy Based on Single‐Atom Manganese Nanozyme

Abstract: Single‐atom nanozymes (SAzymes) can effectively mimic the metal active centers of natural enzymes at the atomic level owing to their atomically dispersed active sites, thereby maximizing atom utilization efficiency and density of active sites. Hence, SAzymes can be considered the most promising candidates to replace natural enzymes. Herein, a PEGylated mesoporous Mn‐based single‐atom nanozyme (PmMn/SAE) employing a coordination‐assisted polymerization pyrolysis strategy that uses polydopamine for photothermal‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 75 publications
2
54
0
Order By: Relevance
“…MB could be oxidized to colorless (oxMB) by • OH, and its concentration could be detected by the absorption peak of 665 nm. 27 As illustrated in Figure 3A 3C) and O 2 production (Figure 3D) confirmed that Cu SAC/NC could significantly catalyze the decomposition of H 2 O 2 to produce • OH and O 2 . 28 In addition, it was found that at pH 7.4, O 2 production was the fastest and most stable (Figure 3E).…”
Section: ■ Results and Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…MB could be oxidized to colorless (oxMB) by • OH, and its concentration could be detected by the absorption peak of 665 nm. 27 As illustrated in Figure 3A 3C) and O 2 production (Figure 3D) confirmed that Cu SAC/NC could significantly catalyze the decomposition of H 2 O 2 to produce • OH and O 2 . 28 In addition, it was found that at pH 7.4, O 2 production was the fastest and most stable (Figure 3E).…”
Section: ■ Results and Discussionsupporting
confidence: 61%
“…To evaluate the catalytic activity of Cu SAC/NC, the catalytic reduction of H 2 O 2 to • OH was monitored by measuring the consumption of substrate methylene blue (MB). MB could be oxidized to colorless (oxMB) by • OH, and its concentration could be detected by the absorption peak of 665 nm . As illustrated in Figure A (inset), Cu SAC/NC + H 2 O 2 made the color of MB change significantly, accompanied by the production of dense bubbles.…”
Section: Resultsmentioning
confidence: 99%
“…41 Besides, doped Yb 3+ ions in the shell have high inherent absorption of NIR photons and intensive energy transfer rate to the luminescent center Er 3+ ions, which can also boost the DC pathway. 42,43 It is reported that the presence of more Yb 3+ ions in the lattice will shorten the distance between Yb 3+ and Er 3+ ions, resulting in energy back-transfer Paper Nanoscale from Er 3+ to Yb 3+ ions. When the Yb 3+ ion content is 20%, the energy transfer efficiency reaches the maximum.…”
Section: Resultsmentioning
confidence: 99%
“…The PEGylated mesoporous Mn‐based single‐atom nanozyme (P m Mn/SAE) is prepared by the coordination assisted polymerization strategy of polydopamine with highly active Mn atoms disperse. [ 53 ] The nanozyme possesses CAT‐, OXD‐, and POD‐like activity. In this regard, P m Mn/SAE nanozymes can not only decompose H 2 O 2 to produce O 2 for easing the hypoxia in the cancer, it can also transfer electrons to O 2 for generate superoxide radicals (•O 2− ) and hydroxyl radicals (•OH) stimulated by Fenton‐like reactions to effective prompt apoptosis of tumor cells.…”
Section: Activity Regulation Strategiesmentioning
confidence: 99%